Employee Performance: An Assessment Model Based on Motivation and Discipline - Priyatna, Soeganda; Erlina; Miswan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
The purpose of this research is to determine the extent of the combined influence of motivation and discipline on employee performance at the West Bandung Regency Education Office Secretariat. The population of this study consists of employees at the West Bandung Regency Education Office Secretariat. The sample used in this study consisted of 38 respondents. The data analysis method employed a quantitative descriptive approach and multiple linear regression analysis using the SPSS tool. Data collection was obtained from respondents through questionnaires. The results of this research indicate that there is an influence of motivation on employee performance, an influence of discipline on employee performance, and a combined influence of motivation and discipline on employee performance at the West Bandung Regency Education Office Secretariat, amounting to 91.8%. This means that motivation and discipline can explain 91.8% of the variation in employee performance at the West Bandung Regency Education Office Secretariat.